EvoDevo - Martindale, Mark Q.; Telford, Max
EvoDevo publishes articles on a broad range of topics associated with the translation of genotype to phenotype in a phylogenetic context. Understanding the history of life, the evolution of novelty and the generation of form, whether through embryogenesis, budding, or regeneration are amongst the greatest challenges in biology. We support the understanding of these processes through the many complementary approaches that characterize the field of evo-devo. The focus of the journal is on research that promotes understanding of the pattern and process of morphological evolution. All articles that fulfill this aim will be welcome, in particular: evolution of pattern formation comparative gene function/expression life history evolution homology and character evolution comparative genomics phylogenetics and palaeontology.